2002
DOI: 10.1046/j.1365-2958.2002.03093.x
|View full text |Cite
|
Sign up to set email alerts
|

The unfolding story of the Escherichia coli Hsp70 DnaK: is DnaK a holdase or an unfoldase?

Abstract: SummaryWe discuss recent experiments that have illuminated individual steps in the reaction cycle of the Escherichia coli Hsp70 molecular chaperone DnaK. Using this new information, we compare two distinctly different global mechanisms of action -holding versus unfolding -and argue that the available evidence suggests that DnaK is an unfoldase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 45 publications
(70 reference statements)
4
84
0
1
Order By: Relevance
“…However, several proteins have been identified that, like IscS, preferentially bind and stabilize a disordered target protein (20)(21)(22). Many of these are chaperone proteins that rescue misfolded proteins (23)(24)(25) or are proteins involved in protein degradation (26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…However, several proteins have been identified that, like IscS, preferentially bind and stabilize a disordered target protein (20)(21)(22). Many of these are chaperone proteins that rescue misfolded proteins (23)(24)(25) or are proteins involved in protein degradation (26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we utilized the E. coli chaperone DnaK. DnaK was purified in the absence of its co-chaperones DnaJ (the DnaK hydrolysis factor) and GrpE (the nucleotide exchange factor) in an ADP-bound state, also referred to as the high affinity state (17)(18)(19)(20)(21). In this form, DnaK binds proteins that expose hydrophobic surface patches.…”
Section: Volume 287 • Number 45 • November 2 2012mentioning
confidence: 99%
“…In addition, several proteins involved in molecular chaperoning (DnaK) (Slepenkov & Witt, 2002), acid tolerance response (YfiD) (Stancik et al, 2002), LPS core region biosynthesis (RfaE) (Valvano et al, 2000), transcriptional regulation and other functions were identified. Interestingly, YbeJ, a putative glutamate/aspartate periplasmic binding and transport protein (Tremoulet et al, 2002) was represented by one of the five unique spots from the wild-type.…”
Section: Proteins Regulated By Yjjqmentioning
confidence: 99%